Analysis of heat and mass transfer in the manufacturing process of instant soy milk using a laboratory scale spray dryer - Nely Ana Mufarida; Asroful Abidin (TURBO [Tulisan Riset Berbasis Online], 2021)
The events that occur during the drying include heat and mass transfer processes. So based on this, this research will discuss "Analysis of Heat and Mass Transfer in the Process of Making Instant Soy Milk Using a Laboratory Scale Spray Dryer". The research method used is the experimental method. The research that will be carried out will consist of preliminary research and main research. The purpose of this preliminary study was to determine the drying air temperature, fogging pressure, and the ratio of soy milk powder to water in solution. The best results from preliminary research are used in the main study. Data processing using technical analysis. The results showed that an increase in the drying air temperature of 80 ° C, 85 ° C, 90 ° C, 95 ° C, and 100 ° C caused a decrease in the need for drying air, namely 27.323 kg of dry air / hour to 9.840 kg of dry air / hour, time the drying of the material is shorter, namely 1 hour 10 minutes to 1 hour, the increase in thermal efficiency is 81.9% to 84.3%, and the increase in product weight coming out of the drying chamber is 3.1 grams to 4.1 grams. The results of the questionnaire showed that the panelists tended to rank taste first (65%), aroma second (61.25%), color third (47.5%).